2006
DOI: 10.1038/sj.jes.7500505
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of pesticide biomarkers between morning void and 24-h urine samples from farmers and their children

Abstract: In pesticide biomonitoring studies, researchers typically collect either single voids or daily (24-h) urine samples. Collection of 24-h urine samples is considered the "gold-standard", but this method places a high burden on study volunteers, requires greater resources, and may result in misclassification of exposure or underestimation of dose due to noncompliance with urine collection protocols. To evaluate the potential measurement error introduced by single void samples, we present an analysis of exposure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…However, this sampling method is burdensome on the study subjects, and non-compliance can lead to compromised or a biased sampling. A common alternative is to collect the first-morning urine, as has been done in many occupational and environmental exposure investigations, because the first-morning urine is often correlated with the 24-hour void (Han et al 2008;Scher et al 2007;Kissel et al 2005). In epidemiological studies such as NHANES involving thousands of participants, first-morning voids are often difficult to obtain; hence, spot urine samples have been used as a more practical solution.…”
Section: Introductionmentioning
confidence: 99%
“…However, this sampling method is burdensome on the study subjects, and non-compliance can lead to compromised or a biased sampling. A common alternative is to collect the first-morning urine, as has been done in many occupational and environmental exposure investigations, because the first-morning urine is often correlated with the 24-hour void (Han et al 2008;Scher et al 2007;Kissel et al 2005). In epidemiological studies such as NHANES involving thousands of participants, first-morning voids are often difficult to obtain; hence, spot urine samples have been used as a more practical solution.…”
Section: Introductionmentioning
confidence: 99%
“…Although 24-h urine sampling is certainly a preferred method for such analyses, it is seldom done for logistical reasons. To evaluate the potential magnitude of errors in using spot urine samples to estimate daily excretion rates, Scher et al (2007) compared the TCPy concentration in 24-h urine collections to "spot" urine samples (first morning void) in farmers and farm children potentially exposed to chlorpyrifos. They concluded that "A consistent bias towards overprediction of pesticide concentration was found among the MVs [morning voids], likely in large part due to the pharmacokinetic time course of the analytes in urine," and noted that this was true for both farmers and their children.…”
Section: Vc5 Limitations Of Use Of Tcpy As a Biomarker For Chlor-mentioning
confidence: 99%
“…In the third study, Scher et al 18 collected first morning voids and 24-h samples from farmers and their children potentially exposed to chlorpyrifos. They measured 3,5,6-trichloro-2-pyridinol (TCP), a chlorpyrifos metabolite, in the first morning void the day following application of chlorpyrifos to a nearby agricultural field, and in the corresponding 24-h void for the day following application.…”
Section: Discussionmentioning
confidence: 99%